PROGRAM AKSI PENANGGULANGAN PENGANGGURAN DI DAERAH ISTIMEWA YOGYAKARTA - Tukiran Tukiran; Endang Ediastuti (Populasi, 1998)
Action programs dealing with unemployment problems, beth by sector and intersector, which were done in the past and those will be done in the future seems are unable to overcome the problems. This is becauce most of the programs were less attracted to the excepted participants (the unemployed). Almost all of the education and training programs offered materials only at introduction level, while in the job seeking competition the preference is a person with a master qualification or on expert in a certain job. The shift of the unemployed characteristics, from the less educated to be an educated one will also simply the action programs' type and level of education and training. It means that the programs should be designed to produce a skilled person or a master on their jobs.